Adverse effects of imatinib in children with chronic myelogenous leukemia - Worawut Choeyprasert (2018)
© 2016 Japan Pediatric Society Background: Imatinib mesylate (IM) is a selective tyrosine kinase inhibitor and is approved for indefinite treatment of pediatric chronic myelogenous leukemia (CML). Potential side-effects regarding growth failure and bone metabolism have been reported but data are still scarce in pediatric CML. Methods: Six chronic-phase CML children on IM treatment with a median age of 9.87 years (range, 5.33–12.67 years) were enrolled in the study. Growth, bone mineral density (BMD), bone parameters, 25(OH)-vitamin D3 (25-OHD3) and blood tests including parathyroid hormone, insulin-like growth factor-1 (IGF-1), IGF binding protein 3, thyroid function test and sex hormones were assessed. Results: Median duration of IM treatment was 78.5 months. Height velocity was suppressed during the first 30 months of treatment and improved gradually afterwards. Two patients (33.3%) had decreased lumbar spine BMD z-scores (<1.5 SD). Patients with decreased BMD had higher mean IM exposure time than those with normal BMD. The majority of patients (n = 5) had low 25-OHD3 (<30 ng/mL), but there was no correlation between BMD and 25-OHD3 status. Other blood tests were normal. Conclusions: This study supports and confirms the need for monitoring the side-effects of IM treatment on growth, bone density and vitamin D status in pediatric CML. Prolonged IM treatment was associated with low BMD without disturbing bone parameters. There was high prevalence of vitamin D insufficiency. Therefore, the beneficial effect of vitamin D supplement should be explored with regard to the effects on height velocity and BMD in CML patients with vitamin D insufficiency.